(untitled) (Journal of Hama University, 2020)
This research aimed to evaluate the efficacy of maxillary molar distalization by the CEOB-1. The sample included 10 unilateral Class II malocclusion patients who had the upper second molar erupted to the occlusal plane. Dentoskeletal changes in patients were evaluated using cephalometric radiographs. The results showed that the CEOB-1 moved the maxillary first molar distally by 3.64 mm accompanied by distal tipping of 11.2°. Also, the maxillary second premolar moved mesially by 1.3 mm with mesial tipping of 3.6°. The results showed that the CEOB-1 provides a good amount of distalization of maxillary molars, in addition to good anchorage control when compared to other appliances with similar anchorage systems. The CEOB-1 is an easy-to-make, inexpensive and effective alternative for maxillary molar distalization, despite the mild anchorage loss